Microwave vs radiofrequency ablation for hepatocellular carcinoma within the Milan criteria: a propensity score analysis. Issue 6 (31st July 2018) - Liu, Wenwu; Zheng, Yun; He, Wei; Zou, Ruhai; Qiu, Jiliang; Shen, Jingxian; Yang, Zhiwen; Zhang, Yuanping; Wang, Chenwei; Wang, Yongjin; Zuo, Dinglan; Li, Binkui; et al.
Summary: Background: Whether microwave ablation (MWA) challenges the standard role of radiofrequency ablation (RFA) in treating early‐stage hepatocellular carcinoma (HCC) remains unclear. Aim: To compare the efficacy of MWA vs RFA for treating primary HCC within the Milan criteria. Methods: From January 2002 to January 2017, the oncological outcomes after MWA (126 patients) and RFA (436 patients) were analysed by propensity score matching. Results: Before propensity score matching, for overall patients, MWA resulted in similar 5‐year overall survival to RFA (80.1% vs 75.8%, P = 0.190) but better 5‐year recurrence‐free survival (28.1% vs 19.6%, P = 0.036). For solitary HCC ≤ 3 cm, MWA resulted in comparable 5‐year overall survival (81.8% vs 77.1%, P = 0.170) to RFA but better 5‐year recurrence‐free survival (34.6% vs 24.0%, P = 0.042). After propensity score matching, MWA resulted in better 5‐year overall survival (79.3% vs 68.4%, P = 0.021) and 5‐year recurrence‐free survival (27.9% vs 6.4%, P < 0.001) than RFA for HCC. For solitary HCC ≤3 cm, MWA resulted in comparable 5‐year overall survival (81.2% vs 66.3%, P = 0.062) and 5‐year recurrence‐free survival (37.7% vs 17.4%, P = 0.088) to RFA. In Cox analysis, RFA modality, tumours located in risk areas and low serum albumin levels were unfavourable prognostic factors for overall survival. RFA modality, multiple tumours, tumour size and low serum albumin levels were unfavourable prognostic factors for recurrence‐free survival (all P < 0.05). Conclusions: RFA is inferior to MWA for treating HCC within the Milan criteria, but has comparable efficacy to MWA for solitary HCC ≤ 3 cm.